2018
DOI: 10.1111/mec.14700
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria and Wolbachia titers are positively correlated during maternal transmission

Abstract: Mothers provide their offspring with symbionts. Maternally transmitted, intracellular symbionts must disperse from mother to offspring with other cytoplasmic elements, like mitochondria. Here, we investigated how the intracellular symbiont Wolbachia interacts with mitochondria during maternal transmission. Mitochondria and Wolbachia may interact antagonistically and compete as each population tries to ensure its own evolutionary success. Alternatively, mitochondria and Wolbachia may cooperate as both benefit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…A recent study demonstrated a positive correlation between Wolbachia and mitochondrial titers in the ovarian tissue of distinct Drosophila and Wolbachia genotypes, with uninfected individuals displaying similar mitochondrial titers as infected flies [ 82 ]. Additionally, Wolbachia titers were unaffected by a decrease in mitochondrial titer, as evidenced by knockdown of mitochondrial genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated a positive correlation between Wolbachia and mitochondrial titers in the ovarian tissue of distinct Drosophila and Wolbachia genotypes, with uninfected individuals displaying similar mitochondrial titers as infected flies [ 82 ]. Additionally, Wolbachia titers were unaffected by a decrease in mitochondrial titer, as evidenced by knockdown of mitochondrial genes.…”
Section: Discussionmentioning
confidence: 99%
“…Further work exploring the impact of manipulating distinct mitochondrial genes on Wolbachia density, in the context of sirt-4 would be of great importance, given the existence of multiple factors affecting mitochondrial energetics in the host [ 83 ]. For instance, the work of Henry [ 82 ] differs from a previous study in which knockdown of the mitochondrial gene NADH dehydrogenase, an enzyme responsible for the conversion of NADH to its oxidized form NAD + (a key substrate in which sirtuin activity relies on), led to a significant reduction in Wolbachia load [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…11,41,42 The evolutionary wileyonlinelibrary.com/journal/ps trajectory of Wolbachia with the host may be obligate symbiosis and it may become an organelle, such as mitochondria. 43 Moreover, Wolbachia reduces species richness but not the evenness of other bacteria, indicating that Wolbachia affects the absolute abundance of other bacteria but not bacterial variation. We speculate that the impact of the recently introduced wStri on bacterial diversity will gradually decrease over future long-term coevolution.…”
Section: Discussionmentioning
confidence: 99%
“…However, in most species, the hosts have only decreased fitness after introducing or removing facultative endosymbionts 11,41,42 . The evolutionary trajectory of Wolbachia with the host may be obligate symbiosis and it may become an organelle, such as mitochondria 43 . Moreover, Wolbachia reduces species richness but not the evenness of other bacteria, indicating that Wolbachia affects the absolute abundance of other bacteria but not bacterial variation.…”
Section: Discussionmentioning
confidence: 99%
“…Since Wolbachia is a strictly cytoplasmic element, it has to establish a sophisticated dialogue not only with the organelles, but also with the nucleus, and even with other infectious organisms, such as the WO phage (LePage et al, 2017). This leads to frequently complex relations with the mitochondria, for example, which may sweep to cytonuclear incompatibilities (Henry and Newton, 2018). The reproductive barriers induced by this bacterium have led it to be considered a speciation agent under some circumstances (Bordenstein et al, 2001; Brucker and Bordenstein, 2012).…”
Section: Introductionmentioning
confidence: 99%